Analysis Of The Impact Of Financial Ratios On The Financial Performance Of Islamic Banking During The Pandemic Period - Ilianto Tri Sagianto; Yulfis Wandi (Dinasti Publisher, 2025)
The objective of this research investigate the impact of five distinct financial elements, specifically BOPO, FDR, NPF, NPM, and ROE, regarding The monetary outcomes of Sharia-compliant banking institutions throughout the widespread health crisis caused by the coronavirus outbreak. The approach used involves quantitative analysis, Assembling data from the financial disclosures of Sharia-compliant banks that are active in Indonesia. The findings suggest that the BOPO variable has no substantial influence on the fiscal outcomes of Sharia-compliant banking institutions, contradicting previous research. These results indicate that although BOPO is often considered an important indicator of bank performance, its influence is not significantly felt in this context. Additionally, The FDR variable does not significantly influence financial performance, although it is expected to serve as an indicator of liquidity and financing efficiency. These results align with some prior studies that note that in certain contexts, FDR does not provide a significant impact. This research offers insights into the challenges faced by Islamic banks during the pandemic and emphasizes the importance of considering external factors in future research that may influence analysis outcomes.